2004
DOI: 10.1111/j.1095-8312.2004.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Vicariance or dispersal? Historical biogeography of three Sunda shelf murine rodents (Maxomys surifer, Leopoldamys sabanus and Maxomys whiteheadi)

Abstract: The Sunda region of south-east Asia comprises the Malay Peninsula and the islands of Java, Sumatra and Borneo, all of which lie on a shallow continental shelf projecting from Indochina. Pleistocene glacial cycles caused sea levels to drop repeatedly, exposing vast areas of the Sunda shelf and creating land bridges among the islands and mainland. These land bridges, the latest of which connected all three of the major Sunda islands to the Malay Peninsula as recently as 9500 years ago, may have enabled mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
154
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 63 publications
9
154
0
Order By: Relevance
“…During glacial periods, when sea level was low, the shelf was widely exposed and arid conditions occurred. However, persistent rain-forest refugia were recently hypothesised to have existed in northern Sumatra, northeastern Borneo and peninsular Malaysia (Brandon-Jones, 1996;Gathorne-Hardy et al, 2002;Gorog et al, 2004). During interglacial periods, when sea level was high, the continent and different islands were isolated, experiencing a widespread tropical climate.…”
Section: Phylogeographical Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…During glacial periods, when sea level was low, the shelf was widely exposed and arid conditions occurred. However, persistent rain-forest refugia were recently hypothesised to have existed in northern Sumatra, northeastern Borneo and peninsular Malaysia (Brandon-Jones, 1996;Gathorne-Hardy et al, 2002;Gorog et al, 2004). During interglacial periods, when sea level was high, the continent and different islands were isolated, experiencing a widespread tropical climate.…”
Section: Phylogeographical Patternmentioning
confidence: 99%
“…These cyclical bottlenecks could have also erased or modified ancestral polymorphism. Such lack of information might explain the inability to resolve basal relationships among clades, as well as the incongruence between Cyt-b and COI markers indicated by the ILD test (Andreev et al, 1998;Gandolfi et al, 2001;Gorog et al, 2004). Seng et al (2001) suggested that the different ecological patterns of A. sundaicus s.l.…”
Section: Phylogeographical Patternmentioning
confidence: 99%
“…When repeated several times throughout the Pleistocene, this system has the potential to generate a lot of diversity. This hypothesis has been supported by low levels of genetic divergence between populations of some Sunda shelf mammals (Campbell et al, 2004(Campbell et al, , 2006Gorog et al, 2004;Lucchini et al, 2005;Roos et al, 2003). However, the vegetation during the Pleistocene glacial periods was undoubtedly very different from the present, and the interactions between climate and sea level and their effects on the distribution of the fauna and flora is complex (van den Bergh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Under this scenario, populations diverge and speciate in allopatry when sea level is high, and then expand their range when sea levels are low and the islands are connected by land (Gorog et al, 2004; see also Steppan et al, 2003). When repeated several times throughout the Pleistocene, this system has the potential to generate a lot of diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation